Pengaruh Kemampuan dan Keterlibatan Pengguna Terhadap Kinerja Sistem Informasi Pengelolaan Keuangan Daerah - Eka Yustikarana, Putu Bayu; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
One manifestation of the application of information technology carried out by the government in the Bali provincial tourism office is improving regional financial management using the Regional Financial Management Information System (SIPKD). Partially needed in the implementation of the system for users who are not involved in the system. Lack of understanding and technical support involving support in the use of SIPKD, which leads to delays in submitting financial reports and answer accountability reports. The aim of the study was to study most user needs and support users in the Regional Financial Management Information System (SIPKD). The method of selecting samples in this study used a saturated sample technique (census). The number of samples in this study were 40 people. Based on published research results regarding the user's ability and positive and significant user support for the performance of SIPKD at the Bali Provincial Tourism Office. Keywords: Use users, user capabilities, SIPKD performance